(untitled) (Konferensiyalar | Conferences, 2024)
The purpose of the article is a theoretical substantiation of the methodology for the formation of lexical skills and abilities of students in teaching a foreign language in the first and second year. The analysis of theoretical approaches helped us to determine the methodological principles in the process of teaching students a foreign language. Language teaching at the first stage should contribute to the components systematic development of foreign language communicative competence, the final formation of which is completed by the graduation, which means the ability and willingness of a specialist to master communication in professional and social life using a foreign language; recognize the need to learn throughout life. In professionally oriented education it is necessary to develop a foreign language course for each industry, which is specific only for this area. skills and abilities that ensure the construction of correct grammatical forms and syntactic constructions. The analysis of this scientific study did not cause controversy.